Comparison of ultra-long gonadotropin releasing hormone agonist versus standard downregulation in women with adenomyosis undergoing frozen-thawed embryo transfer: a randomized clinical trial - Soheila Ansaripour; Katayoun Yazdchi; Mohammad Reza Sadeghi; Nasim Nasseri; Atousa Karimi; Mina Ataei; Narges Madadi; Fateme Jalalinejad; Fahimeh Rahimi (BMC, 2024)
Abstract Background Adenomyosis can lead to infertility and failure of in vitro fertilization. Limited evidence suggests that the use of long-term treatment with gonadotropin-releasing hormone (GnRH) agonists followed by frozen-thawed embryo transfer (FET) may be the preferred approach for women with adenomyosis. Objective The aim of this randomized controlled trial is to compare the efficacy of an ultra-long GnRH agonist with standard downregulation in women with adenomyosis undergoing FET. Materials and methods This randomized controlled trial enrolled 72 women with adenomyosis diagnosed by sonographic criteria who underwent FET cycles at the Avicenna Infertility Center. These women were randomly assigned to two equal groups: one received GnRH agonist treatment for three months before the FET cycle and the other served as the standard downregulation group. Results were reported as chemical and clinical pregnancy rates. Results The two groups were similar in age, body mass index, anti-Müllerian hormone levels, number of previous pregnancies and miscarriages, presence of uterine myomas, and endometriosis. However, the total dose of estradiol used until embryo transfer was significantly higher in the ultra-long GnRH agonist group than in the standard group (96.14 mg vs. 80.52 mg, p-value = 0.004). Nevertheless, chemical and clinical pregnancy rates did not differ significantly between the two groups. Conclusions Ultra-long GnRH agonist downregulation did not improve the chemical and clinical pregnancy rate in the FET cycle in women with adenomyosis compared with standard GnRH agonist downregulation in the other words, ultra-long GnRH agonist downregulation is not superior to standard protocol. In women with adenomyosis (without history of endometriosis), downregulation of standard GnRH agonists prior to frozen-thawed embryo transfer may be the preferred embryo transfer protocol to gain higher clinical/chemical pregnancy rate. Trial registration Clinical trial registry: IRCT20160717028967N9, available at: https://irct.behdasht.gov.ir/trial/36103 .